Effective and Efficient Elementary School Management Strategies - Amri, Rofi Ul; Inganah, Siti (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2025)
Effective and efficient elementary school management is the key to improving the quality of elementary education in Indonesia. This study aims to describe the actual conditions of elementary school management, identify appropriate management strategies, and analyze supporting and inhibiting factors in their implementation. The method used is descriptive qualitative research with data collection techniques through interviews, observations, and documentation in several selected elementary schools. The results of the study indicate that effective elementary school management is characterized by visionary principal leadership, data-based program planning, and active involvement of all school members. Meanwhile, efficiency is reflected in the optimization of resources, the use of information technology, and collaboration with external parties. The main supporting factors are policy support, management training, and a collaborative work culture. Meanwhile, the obstacles found include limited funds, lack of ongoing training, and resistance to innovation. This study concludes that contextual, participatory, and adaptive management strategies are needed to realize quality and sustainable elementary education.